baby care book : A Complete Guide from Birth to 12 Months Old - Friedman, Jeremy, Dr.; Saunders, Norman, Dr. (Toronto, Ontario : Robert Rose Inc., 2007)
A clear, thoughtful and objective guide written by pediatricians from a major children's hospital provide a complete overview of caring for babies in their first year.
Includes index.
The Hospital for Sick Children.
Keywords: Pediatrics -- Popular works; Infants -- Health and hygiene; Infants -- Care